The tempest - Shakespeare, William, 1564-1616.; Gibson, Rex. (Cambridge : Cambridge University Press, 1995)
Presents the text of Shakespeare's play which focuses on Prospero, the deposed Duke of Milan, who is exiled on a remote island with his daughter, Miranda. Includes notes and criticism on the play, and a general discussion of Shakespeare's life.
Book Report.
Young Adult
Keywords: Shakespeare, William, -- 1564-1616.; Shakespeare, William, -- 1564-1616 -- Criticism and interpretation; Shakespeare, William, -- 1564-1616.; English drama -- History and criticism; Young adult drama, English; English drama -- History and criticism